2022
DOI: 10.1186/s12903-022-02146-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluoride iontophoresis on seal ability of self-etch adhesive in human dentin in vitro

Abstract: Background Fluoride iontophoresis (FI) is a non-invasive method for the transfer of fluoride ions under electrical pressure into dental hard tissue. This study aimed to determine the effect of FI on the seal ability of self-etch adhesive in human dentin using dentin permeability test and scanning electron microscopy (SEM). Methods The experiments were divided into 2 series: series 1 was performed on 28 extracted intact third molars and series 2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Recently, Kijsamanmith et al 30 demonstrated that fluoride iontophoresis with a neutral 2% sodium fluoride solution had no negative effect on the seal ability of self-etch adhesive in human dentin, when compared to without fluoride iontophoresis. Also, it could improve the seal ability of the self-etch adhesive in intact dentin better than that in caries affected dentin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kijsamanmith et al 30 demonstrated that fluoride iontophoresis with a neutral 2% sodium fluoride solution had no negative effect on the seal ability of self-etch adhesive in human dentin, when compared to without fluoride iontophoresis. Also, it could improve the seal ability of the self-etch adhesive in intact dentin better than that in caries affected dentin.…”
Section: Discussionmentioning
confidence: 99%
“…After that, 26 specimens were randomly divided into 4 groups; Group 1: SnF 2 without-iontophoresis ( n = 10), 0.429% SnF 2 toothpaste (1040 ppm; GSK group of companies, UK) was applied on a moist occlusal dentin surface and agitated with an applicator brush for 1 min and left undisturbed for 4 min. Group 2: SnF 2 with-iontophoresis ( n = 10), occlusal dentin surface was applied with SnF 2 toothpaste and treated with cathode iontophoresis using an iontophoresis device (DENTAPHOR™-II MODEL 6111D, Life-Tech Inc ® , USA) at electrical current 0.5 mA for 5 min 30 . Group 3: no SnF 2 without-iontophoresis ( n = 3), distilled water was applied on a moist occlusal dentin surface and agitated with an applicator brush for 1 min and left undisturbed for 4 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some drugs, e.g., lignocaine or sodium fluoride, are already administered by iontophoresis to patients effectively. Others like dexamethasone, 5-fluorouracil, leucovorin, lidocaine, nicotine, ondansetron, metronidazole, acyclovir, amikacin, gentamicin sulfate, ciprofloxacin, amoxicillin, ketoconazole, fentanyl hydrochloride, diclofenac sodium, ibuprofen, naproxen sodium, and potassium iodide are under in vitro investigations or undergoing animal studies and have shown potential for applying them for delivery them [ 40 , 42 , 43 , 67 , 86 , 87 ]. To facilitate the iontophoretic transport of ions into the enamel, two devices were developed: Fluorinex® (for sodium fluoride) and “electrically accelerated and enhanced remineralization” (EAER®) [ 30 , 56 , 66 ].…”
Section: Medical Devicesmentioning
confidence: 99%
“…It is used in dentistry to create an electro-analgetic impact; it facilitates the ionic movement of the desensitizing material from a high concentration to a low concentration within the dentinal tubules with the help of an electric current, and it blocks the dentinal tubules [ 27 , 28 , 29 , 30 , 31 ]. Fluoridated desensitizers are the most frequently used desensitizers when treating DH with iontophoresis [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%